Daur Ulang Limbah dalam Pandangan Hukum Islam - Sa'diyah, Halimatus (JURNAL AT-TURAS, 2018)
The waste recycling is a process in which the new products are made from used products to provide more benefits for human being and to maintain the sustainable ecosystem. It is based on theological assumption that a waste, whatever bad of it, is a part of nature as inseperable way of God’s creation. This article argues that recycling process is human’s responsibility to serve the earth with reorganizing and reusing every possible useable things into commodities or others. As a part of prodoct which is possible to be purified (mutanajjis in Islamic term), a waste could be utilized to the useful products for human. Islam, for this term, also ruled the essence of human brain to make use God’s creation.